МОНГОЛ ОРНЫ ЗАРИМ НУУРЫН ЭМЧИЛГЭЭНИЙ ШАВРЫН БАЛЬНЕОЛОГИЙН СУДАЛГАА - Долмаа, Ганиа; Баяраа, Батнасан; Энхбадрал, У; Ганзаяа, Ганхүрэл; Номинцэцэг, Бямбажав (Proceedings of the Mongolian Academy of Sciences, 2016)
The peloids are the important natural remedy all over the world. Balneological and physical properties of eight Mongolian peloids collected from Lake Khyaraan (Selenge province), Tushigtsagaan (Selenge province) and Nogoon (Gobi-Altai province), Lake Kholboolj (Bayankhongor province), Lake Khundagan (Tuv province), Lake Tsaidam and Nokhoi Unadag (Arkhangai province), Lake Gurvan nuur (Khentii province), have been studied using analytical techniques. According the research we have determined physical properties of peloids from eight lakes (specific weight, moisture, porosity and moisture capacity) and balneological properties (liminess, thermal conductivity, heat capacity and the ability to retain heat) respectively. In result of the research, the physicochemical characteristics of the peloids are correcting standard satisfactory which treatment needs.